Jinfukang regulates integrin/Src pathway and anoikis mediating circulating lung cancer cells migration. (1st March 2021) - Que, Zu-Jun; Yang, Yun; Liu, Hai-Tao; Shang-Guan, Wen-Ji; Yu, Pan; Zhu, Li-Hua; Li, He-Gen; Liu, Huai-Min; Tian, Jian-Hui
Abstract: Ethnopharmacological relevance: Metastasis is the main cause of death in lung cancer patients. Circulating tumor cells (CTCs) may be an important target of metastasis intervention. Previous studies have shown that Jinfukang could prevent the recurrence and metastasis of lung cancer, and we have established a circulating lung tumor cell line CTC-TJH-01. However, whether Jinfukang inhibition of lung cancer metastasis is related to CTCs is still unknown. Aim of the study: To further explore the mechanism of Jinfukang in anti-metastasis of lung cancer from the perspective of intervention of CTCs. Materials and methods: CTC-TJH-01 and H1975 cells were treated with Jinfukang. Cell viability was detected by CCK8, and the cell apoptosis was detected by flow cytometry. Transwell was used to detected cell migration and invasion. Cell anoikis was detected by anoikis detection kit. Protein expression was analysis by Western blot. Results: Jinfukang could inhibit the proliferation, migration and invasion of CTC-TJH-01 and H1975 cells. Besides, Jinfukang could also induce anoikis in CTC-TJH-01 and H1975 cells. Analysis of the mRNA expression profile showed ECM-receptor interaction and focal adhesion were regulated by Jinfukang. Moreover, it was also find that Jinfukang significantly inhibited integrin/Src pathway in CTC-TJH-01 and H1975 cells. When suppress the expression of integrin with ATN-161, it could promote Jinfukang to inhibit migration and induce anoikis in CTC-TJH-01 and H1975 cells. Conclusions: Our results indicate that the migration and invasion of CTCs are inhibited by Jinfukang, and the mechanism may involve the suppression of integrin/Src axis to induce anoikis. These data suggest that Jinfukang exerts anti-metastatic effects in lung cancer may through anoikis. Graphical abstract: Image 1